PENINGKATAN KECERDASAN LOGIKA MATEMATIKA DI TAMAN KANAK-KANAK GEMBALA BAIK PONTIANAK - Sutini, Maria Geroti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The purpose of this study to increase intelligence through the use of mathematical logic game find match picture in children aged 5-6 years with descriptive methods. In general it can be concluded that: 1) Planning of learning by using the find match game to improve intelligence picture mathematical logic in children aged 5-6 years are categorized as